The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1029/2020tc006561
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous Provenance, Sediment Dispersal, and Foreland Basin Development in Southwestern Montana, North American Cordillera

Abstract: Retroforeland basins form adjacent to fold-thrust belts and contain the stratigraphic record of mountain building (DeCelles, 2012;Ingersoll, 2012). In some cases, where portions of the hinterland have been displaced along major strike-slip faults, the foreland basin system may hold key information for unraveling complex geological histories as it remained stationary on the continent during orogenesis (e.g., Wyld et al., 2006). During Early Cretaceous time, the western margin of the Idaho-Montana sector of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 135 publications
0
39
0
1
Order By: Relevance
“…Our mixture model for the Group 2 U-Pb detrital zircon composite (Figure 9b) suggests a similar, but slightly more complex provenance than that of the underlying Kootenai Formation (Rosenblume et al, 2021). The Group 2 mixture model includes ages between 200 and 3500 Ma; it results in a best fit with R 2 = 0.926 and indicates major contributions of 39% Ordovician-Devonian-Mississippian, 18% Cambrian, 17% Kootenai Formation and minor contributions from other potential source strata.…”
Section: Group 2 Provenance-lowermiddle Palaeozoic Strata In Idaho Se...mentioning
confidence: 77%
See 3 more Smart Citations
“…Our mixture model for the Group 2 U-Pb detrital zircon composite (Figure 9b) suggests a similar, but slightly more complex provenance than that of the underlying Kootenai Formation (Rosenblume et al, 2021). The Group 2 mixture model includes ages between 200 and 3500 Ma; it results in a best fit with R 2 = 0.926 and indicates major contributions of 39% Ordovician-Devonian-Mississippian, 18% Cambrian, 17% Kootenai Formation and minor contributions from other potential source strata.…”
Section: Group 2 Provenance-lowermiddle Palaeozoic Strata In Idaho Se...mentioning
confidence: 77%
“…Grey-shaded region highlights the study interval, which is separated into a western and eastern region based on previous work (Schwartz, 1972). Maximum depositional ages of underlying Kootenai Formation are based on previous work Rosenblume et al, 2021) Blackleaf locality to provide context for samples (Figure 3), which are identified by an abbreviation for the locality followed by the stratigraphic level in metres from which they were collected. For the sample at the Buffalo Jump locality (Table 1; KcBJ), a stratigraphic section was not measured.…”
Section: Field Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absolute age of deformation within these two packages is less constrained. A basal angular unconformity, isopach maps, and reconstructed paleocurrent data from the lower‐Cretaceous to mid‐Cretaceous Kootenai Formation in the southwestern Montana foreland may suggest early, low‐magnitude exhumation related to thick‐skinned thrusting (Decelles, 1986; Scholten, 1982; Schwartz, 1982), but within a regionally continuous foreland basin setting with extrabasinal sources (Rosenblume et al., 2021). Provenance studies of the Late Cretaceous to Paleocene Beaverhead Group (Garber et al., 2020; Haley et al., 1991; Perry & Sando, 1982; Ryder & Scholten, 1973) and low‐temperature thermochronologic data (Carrapa et al., 2019) suggest mid to Late Cretaceous exhumation of the Blacktail‐Snowcrest arch, followed by in‐sequence slip along the thin‐skinned Medicine Lodge and Tendoy thrusts.…”
Section: Introductionmentioning
confidence: 99%